Desain Bahan Ajar pada Pembelajaran Outdoor Class untuk Meningkatkan Keterampilan Berpikir Kritis Peserta Didik - Sitti Zakiyah Azinah A; Subaer; Muhammad Arsyad (Postgraduate, University of Mataram, 2024)
This type of research is Research and Development (R&D). This study aims to design teaching materials for outdoor class learning. The results of the study showed that expert research on teaching materials for outdoor class learning that had been developed was then analyzed using the Aiken'V formulation, obtaining an average aspect of content feasibility of 0.82, presentation feasibility of 0.84 and language aspect of 0.78 and declared to meet the feasibility criteria (valid). The results of the teacher's assessment of the teaching materials obtained aspects of the feasibility of instructions with an average of 3.67, aspects of the coverage of questionnaire components of 3.67 and aspects of language feasibility of 3.33 with a very practical category. So, it can be concluded that the teaching materials in this outdoor class learning are declared worthy of being tested. The effectiveness of teaching materials in outdoor class learning can be seen from the increase in critical thinking skills of students based on the results of the pretest and posttest which were analyzed using the N-Gain test. Overall, the average value of students' N-Gain in critical thinking skills is 0.61 in the moderate category. So, it can be concluded that there is an increase in critical thinking skills of class XI students of SMAN 3 Enrekang. This shows that teaching materials in outdoor class learning are effective for use in the learning process.